KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BARITO TIMUR - Nika Nurpersi; Lili Safrida; Kadir (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2022)
Restaurant tax is one of the sources of revenue that contributes to the increase in PAD. The purpose of this study is to determine the contribution of restaurant taxes to local revenue, especially in East Barito Regency. The data source is secondary data through the Regional Revenue Agency of East Barito Regency. Data collection techniques with documentation and analysis techniques, namely the analysis using quantitative analysis tools. From the results of the research, the realization of restaurant taxes in East Barito Regency in 2019-2021 is classified as fluctuating. With respect to local taxes, restaurant tax contributions fluctuated from 2019-2021 while local revenue from 2019-2021 continued to decline due to the high realization of local revenue.